Perceiving Social Cohesion: Movement Synchrony and Task Demands Both Matter. (April 2019) - Wilson, Stuart; Gos, Caroline
Previous research has shown that interpersonal synchrony is associated with a number of prosocial effects. We investigated the respective roles of behavioural synchrony and perceived task demands on perceptions of cohesion by performing two experiments in which participants viewed pairs of point-light figures engaging in four coordinated behaviours. Behaviours were seen twice, once in perfect in-phase synchrony and once with synchrony manipulated (phase shift: 180° in Experiment 1 and 45°, 90°, 270°, and 315° in Experiment 2). Dyads were rated on perceived exertion and perceived social cohesion. Results indicate that in-phase synchrony is associated with higher levels of perceived cohesion and that perceived exertion is a good predictor of cohesion ratings. Two interactions suggest that the effect is not purely perceptual and that participants observing coordinated movement also make inferences about the intentions of those observed. Results are discussed and future directions suggested.